Interfacial Engineering of PVDF‐TrFE toward Higher Piezoelectric, Ferroelectric, and Dielectric Performance for Sensing and Energy Harvesting Applications. Issue 6 (3rd January 2023) - Abdolmaleki, Hamed; Haugen, Astri Bjørnetun; Buhl, Kristian Birk; Daasbjerg, Kim; Agarwala, Shweta
Abstract: The electrical properties of pristine fluoropolymers are inferior due to their low polar crystalline phase content and rigid dipoles that tend to retain their fixed moment and orientation. Several strategies, such as electrospinning, electrohydrodynamic pulling, and template‐assisted growing, have been proven to enhance the electrical properties of fluoropolymers; however, these techniques are mostly very hard to scale‐up and expensive. Here, a facile interfacial engineering approach based on amine‐functionalized graphene oxide (AGO) is proposed to manipulate the intermolecular interactions in poly(vinylidenefluoride‐trifluoroethylene) (PVDF‐TrFE) to induce β ‐phase formation, enlarge the lamellae dimensions, and align the micro‐dipoles. The coexistence of primary amine and hydroxyl groups on AGO nanosheets offers strong hydrogen bonding with fluorine atoms, which facilitates domain alignment, resulting in an exceptional remnant polarization of 11.3 µC cm −2 . PVDF‐TrFE films with 0.1 wt.% AGO demonstrate voltage coefficient, energy density, and energy‐harvesting figure of merit values of 0.30 Vm N −1, 4.75 J cm −3, and 14 pm 3  J −1, respectively, making it outstanding compared with state‐of‐the‐art ceramic‐free ferroelectric films. It is believed that this work can open‐up new insights toward structural and morphological tailoring of fluoropolymers to enhance their electrical and electromechanical performance and pave the way for their industrial deployment in next‐generation wearables and human‐machine interfaces. Abstract : In this research, a facile interfacial engineering approach based on amine‐functionalized graphene oxide (AGO) is presented to improve the electrical properties of fluoropolymers. It is shown that AGO incorporation can lead to a higher β / α ratio and larger lamellae dimensions, which is translated into higher remnant polarization, and larger longitudinal piezoelectric coefficient in PVDF‐TrFE.